Correlation between Quantumchemically Calculated LUMO Energies and the Electrochemical Window of Ionic Liquids with Reduction-Resistant Anions - Wim Buijs; Geert-Jan Witkamp; Maaike C. Kroon (International Journal of Electrochemistry)
Quantum chemical calculations showed to be an excellent method to predict the electrochemical window of ionic liquids with reduction-resistant anions. A good correlation between the LUMO energy and the electrochemical window is observed. Surprisingly simple but very fast semiempirical calculations are in full record with density functional theory calculations and are a very attractive tool in the design and optimization of ionic liquids for specific purposes.